The Crisis of the Public Monument: Architectural Models and Memory Strategies - Del Sole, Francesco (Actual Problems of Theory and History of Art, 2022)
The 20th century generated a crisis of public monuments. This paper proposes a reflection on the choices made by the society regarding what aspects of history to remember and how to provide a foundation for its collective identity. Since ancient times, the task of public monuments has been to imprint in history the perpetual memory of a character, identified as the ideal model around which the history of their time revolves. With the French Revolution, there was a fundamental change of course on this front. The public no longer needed to follow an ideal sovereign, and the story was no longer calibrated to a single character but to each citizen. The crisis of public monuments after World War II dealt with the concept of durability, a fundamental attribute for this archetype, with the consequent birth of the counter-monument. To fully understand this crisis, the evolution of one of the commemorative monuments par excellence — historiated column — will be analysed through three key examples, far apart in space and time, each exemplifying a precise evolutionary phase: Trajan’s Column, the Vendôme Column, and the Monument against Fascism, erected in 1986 by Esther Shalev-Gerz and Jochen Gerz.